Biochemistry of the Thrombin-Like TLBpic and Its Purification from Bothrops pictus “Jergon de la Costa” (Reptilia: Viperidae) - Victor Ludgardo Álvarez Tohalino; Hugo Guillermo Jiménez Pacheco; Juan Raúl Jesús Zumaran Farfán; Pavel Kewin Delgado Sarmiento; Paulino Rodolfo Zegarra Panca (Journal of Chemistry)
The venom of snakes is composed of a heterogeneous mixture of simple and complex substances, with inflammation and hyperalgesia being the first symptom caused by the action of Bothrops venom, generating processes such as leukocyte infiltration, hemorrhage, and the intravascular formation of thrombi. Within the simple substances, we have free amino acids, peptides, nucleotides, carbohydrates, lipids, and biogenic amines (organic molecules) as well as cations and anions (inorganic constituents). Of the ions, we can highlight calcium, which is an important cofactor of some proteolytic enzymes as well as phospholipases A2. And magnesium and zinc are important cofactors of venom metalloproteases. Complex substances are related to proteins and enzymes. Studies related to the total venom of snake present in several organic substances act as pain mediators and are called biogenic amines, such as bradykinin, histamine, 4-hydroxytryptamine, N-methyl-5-hydroxytryptamine, N′-N′-dimethyl-5-hydroxytryptamine, and serotonin. In the present study, a fraction with serinoprotease and coagulant activity has been purified on fibrinogen, called TLBpic, using a cationic ion exchange chromatographic system coupled to an HPLC system. The main characteristic of our protocol is the speed, and the high recovery of the fraction with optimal terms gave result of evidence in the SDS-PAGE gel. The ESI (electrospray ionisation), corresponding to the electrophoresis of proteins in polyacrylamide gels and to their denaturing solubilization in the presence of the SDS ionic detergent, uniting the proteins, breaking hydrophobic interactions, showing a molecular mass of ∼30 kDa, demonstrating high molecular homogeneity that exists in this family of proteins, is a soft ionization method, in which the samples were ionized by the addition or removal of a proton, with very little extra energy to cause fragmentation of the produced ions. Samples with molecular masses greater than 1200 Da originate multicharged ions (M + nH)n+ in the positive ionization mode; this methodology guarantees that the purified material has a high degree of purity.